การสังเคราะห์และการอัดแน่นวัสดุผสมเหล็กอะลูมิไนด์เสริมแรงด้วยไทเทเนียมไดบอไรด์และอะลูมิเนียมออกไซด์โดยกระบวนการปฏิกิริยาก้าวหน้าด้วยตัวเองที่อุณหภูมิสูงร่วมกับกระบวนการกระแสไฟฟ้าในการช่วยซินเทอริง - สุธรรม นิยมวาส (มหาวิทยาลัยสงขลานครินทร์, 2024)
The purpose of the investigation was to synthesize the ceramic composite from the ilmenite (FeTiO3), boron oxide (B2O3) and aluminum (Al), which divided into two parts. In first part of the experiment was to study the effects of Al molar ratio (4 4.33 and 5 mole) and milling duration of FeTiO3 + B2O3 system (0.5 1 and 1.5 hr) with a compaction force of green pellet (60 80 and 100 MPa) on the self propagation high-temperature synthesis reaction phenomena. In the second part, was to study effects of compaction force of green pellet inside a graphite mold including electric current supply and a charging time from the induction heat machine as well as a study effect of the compaction force of the product in-situ red hot phenomena. In addition, mechanical and thermal properties of the composite product were investigated. The experimental results of self propagation high-temperature synthesis showed that, the addition of Al molar ratio to form completely FeAl3-TiB2-Al2O3 composite. The fastest self propagated rate was achieved at 0.63 mm/s when the milling duration of FeTiO3 + B2O3 was 1.5 hr and the compaction force of green pellet was 100 MPa. The experimental results of in-situ combustion synthesis and consolidation showed that the best compaction force of pellet inside a graphite mole was 3900 MPa. Charging current and charging time was 450 A and 4 min, respectively. The micro-hardness of matrix phase (FeAl3+Al2O3) and reinforcement phase (TiB2) was 468.22 Hv and 818.78 Hv, when apply the compaction force 3250 MPa